(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the significance of dictionaries in the process of learning English as a foreign language. Learning a foreign language is a complex cognitive process that involves acquiring not only vocabulary but also pronunciation, grammar, and cultural understanding. Among the essential tools that facilitate this process, dictionaries occupy a central position. This article explores the crucial role dictionaries play in learning English as a foreign language and highlights their contribution to vocabulary development, comprehension, and communicative competence. Dictionaries are not merely collections of words and definitions—they serve as comprehensive linguistic guides that help learners understand how words function in real contexts. The study examines various types of dictionaries, including bilingual, monolingual, specialized, and digital, and analyzes how each type assists learners at different proficiency levels. The paper also emphasizes the pedagogical benefits of dictionary use: expanding vocabulary, improving pronunciation through phonetic transcription, learning correct spelling, and recognizing collocations and idiomatic expressions. Furthermore, the integration of modern digital dictionaries and mobile applications has revolutionized the learning process by providing instant access to updated definitions, audio pronunciation, and interactive examples. However, the study also notes the importance of balanced and critical use of dictionaries to avoid overreliance on translation and to develop independent language learning strategies. Ultimately, effective and informed use of dictionaries enhances learners’ linguistic awareness, promotes autonomy, and contributes to their overall mastery of the English language.